Magneto-mechanical analysis of magnetic gear pole pieces ring from analytical models for wind turbine applications. Issue 4 (August 2018) - Desvaux, M; Multon, B; Ahmed, H Ben; Sire, S
This article deals with the structural behavior of a multi-bar system which maintains pole pieces in a concentric magnetic gear. Simplified analytic magnetic and mechanical models of the system are proposed in order to be integrated in a multi-criteria global optimization for the sizing of a magnetic gear in wind power applications. For this purpose, the reduction of the computation time is taken into account. The geometry of the support bar subsystem is defined and a Q bar structure is proposed. The magnetic study is based on Maxwell's equations and subdomain method in order to determine variable radial and tangential magnetic loads. The mechanical study is based on a multibody model with different bars stiffnesses which are determined from a one-dimensional model. Variable radial and tangential magneto-mechanical pole pieces loads (magnetic load and weight) are also considered. An example of a magnetic gear with 172 pole pieces (i.e. 6-MW wind turbine) is proposed to analyze the mechanical behavior and also the computation time.